The Implementation Of Tongue Twister Technique For Students' Pronunciation Of English Consonant Sounds At SMA Zainul Hasan 1 Genggong - Nur Aini; Muhammad Hifdil Islam; Benny Hamdani (Innovative: Journal Of Social Science Research, 2023)
This study intends to determine how the tongue twister technique is used to teach pronunciation at SMA Zainul Hasan 1 Genggong, as well as what benefits and drawbacks can be found from using it to improve students' pronunciation abilities. With a case study research design, the researcher in this instance used a qualitative descriptive analysis method. Two research tools, namely observation and interviews, were employed to gather data. For the academic year 20222023, the class X pupils at SMA Zainul Hasan 1 Genggong served as the research object. The study's findings indicate that while using the tongue twister approach to teach pronunciation, teachers employ two types of techniques: first, requiring students to watch a video that the teacher has created and pronounce each tongue-twister that is shown in the video and second requiring students to recite and imitate examples of several sentences of tongue-twisters that the teacher has written in blackboard. Meanwhile, using the tongue twister approach offers benefits like: it improves pupils' fluency while reciting a sentence, is entertaining, demanding, and doesn't get old easily. The tongue twister technique has some drawbacks, such as the need for patience from the teacher when employing it, and the length of time it takes to apply. Keywords: pronunciation technique, English consonant sounds, tongue twister.